Thin superior flap in mammoplasty procedures - Humberto Campos (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: For being one of the procedures mostly performed in our environment, breast plastic surgery involves many technical variations and surgical strategies that provide the plastic surgeon with several options. The objective of this study was to evaluate the use of thin superior flap technique in mammoplasties. METHODS: Over a period of 2 years, we selected 30 patients presenting with mammary hypertrophy and/or breast ptosis. A technique based on the inverted-T marking and Ribeiro's type IV inferiorly based flap was carried out. The intervention involved the production of a thin superior flap with a thickness of approximately 2 cm. This comprised 30% of the breast volume, while the inferior flap was responsible for the remaining 70%. RESULTS: Three expert plastic surgeons evaluated the patients. The results showed that 91.5% of the women who underwent this procedure presented with excellent quality outcomes, while 6.9% had a good outcome. Further, a fair outcome was observed only in 1.6% of the patients, while poor outcomes were not obtained. The procedure had a complication rate of 2.6%, which included one case of infection, one of asymmetry, and two of unsightly scars. CONCLUSION: The thin superior flap proved to be very effective in mammoplasties.